Culture of the copy : striking likenesses, unreasonable facsimiles - Schwartz, Hillel, 1948- (Zone Books, 2014)
"The Culture of the Copy is an unprecedented attempt to make sense of the Western fascination with replicas, duplicates, and twins. Hillel Schwartz charts the repercussions of our entanglement with copies of all kinds, whose presence alternately sustains and overwhelms us. Through intriguing, and at time humorous, historical analysis and case studies in contemporary culture, Schwartz investigates a stunning array of simulacra - counterfeits, decoys, mannequins, and portraits; ditto marks, genetic cloning, war games, and camouflage; instant replays, digital imaging, parrots, and photocopies; wax museums, apes, and art forgeries, not to mention the very notion of the Real McCoy. His examination of a wide range of modernist, feminist, and postmodern theories about replication and mechanical reproduction culminates with the following compelling question: How have the ethical dilemmas central to so many fields of endeavor become inseparable from the pursuit of copies - of the natural world, or our own creations, indeed of our very selves? This book is an innovative blend of micro-sociology, cultural history, and philosophical reflection of interest to anyone concerned with problems of authenticity, identity, and originality."--Jacket